Stimuli context and context of expectations – which one has more influence on pain perception - Ružić, Valentina (Array, 2014)
In the field of psychophysics research, if stimuli are presented in mixed series of different intensities, effects of stimulus context may appear. For example, the assessment of a particular stimulus intensity may depend on the intensities of other stimuli in the series. Outside the psychophysical context, the perception of the intensity (especially of painful stimuli) can be modulated by numerous additional cognitive factors. One of the most prominent is the expectation of pain intensity that will occur. The aim of this study was to investigate the influence of psychophysically manipulated stimuli context and verbally manipulated expectations on perception of weak and strong electrocutaneous pain stimuli. The experimental design involved four independent groups. Groups were previously counterbalanced regarding painful sensitivity. The first experimental group received a series of weak electrocutaneous stimuli, and was verbally instructed that they will receive weak painful stimuli. The second group received the same series of weak stimuli, and were told that they will receive strong painful stimuli. The third group received a series of strong painful stimuli, and were told that they will receive weak painful stimuli. The fourth group received a series of strong painful stimuli, and were told that they will receive strong painful stimuli. So, for the two groups the intensity level of the stimuli in the series was in accordance with verbally manipulated expectations, and in other two it was not. The four strongest stimuli intensities from weak series were the weakest stimuli in the strong series. Using such a design, we were able to observe the effect of stimuli context, i.e., estimation of the same intensities in different series of intensities on the one hand, and the effect of expectation on the other. Participants estimated the intensity of the stimulus on a verbal analogue scale of 30 units. The results showed that there was no effect of manipulated stimulus context. The same stimulus intensities, when they were the weakest in series or as the strongest in the series, on occasions when verbally manipulated expectations were consistent with intensity of series were estimated equally intense. However, the results showed a clear influence of the expectations manipulated by verbal instruction. When the series was weak and has been suggested to be strong, the estimates were in line with expectations manipulated. They estimated weak stimuli as very strong. When participants received objectively strong stimuli, and were informed that they were weak, they estimated them as very weak. The results suggest a strong influence of verbally manipulated expectation on pain perception, while psychophysical context had no effect.